Population-Genomic Insights into Variation in Prevotella intermedia and Prevotella nigrescens Isolates and Its Association with Periodontal Disease - Zhang, Yifei; Zhen, Min; Zhan, Yalin; Song, Yeqing; Zhang, Qian; Wang, Jinfeng (Frontiers in Cellular and Infection Microbiology, 2017)
High-throughput sequencing has helped to reveal the close relationship between Prevotella and periodontal disease, but the roles of subspecies diversity and genomic variation within this genus in periodontal diseases still need to be investigated. We performed a comparative genome analysis of 48 Prevotella intermedia and Prevotella nigrescens isolates that from the same cohort of subjects to identify the main drivers of their pathogenicity and adaptation to different environments. The comparisons were done between two species and between disease and health based on pooled sequences. The results showed that both P. intermedia and P. nigrescens have highly dynamic genomes and can take up various exogenous factors through horizontal gene transfer. The major differences between disease-derived and health-derived samples of P. intermedia and P. nigrescens were factors related to genome modification and recombination, indicating that the Prevotella isolates from disease sites may be more capable of genomic reconstruction. We also identified genetic elements specific to each sample, and found that disease groups had more unique virulence factors related to capsule and lipopolysaccharide synthesis, secretion systems, proteinases, and toxins, suggesting that strains from disease sites may have more specific virulence, particularly for P. intermedia. The differentially represented pathways between samples from disease and health were related to energy metabolism, carbohydrate and lipid metabolism, and amino acid metabolism, consistent with data from the whole subgingival microbiome in periodontal disease and health. Disease-derived samples had gained or lost several metabolic genes compared to healthy-derived samples, which could be linked with the difference in virulence performance between diseased and healthy sample groups. Our findings suggest that P. intermedia and P. nigrescens may serve as “crucial substances” in subgingival plaque, which may reflect changes in microbial and environmental dynamics in subgingival microbial ecosystems. This provides insight into the potential of P. intermedia and P. nigrescens as new predictive biomarkers and targets for effective interventions in periodontal disease.